2017
DOI: 10.1142/s0218195917600056
|View full text |Cite
|
Sign up to set email alerts
|

Improved Approximation for Fréchet Distance on c-Packed Curves Matching Conditional Lower Bounds

Abstract: The Fréchet distance is a well studied and very popular measure of similarity of two curves. The best known algorithms have quadratic time complexity, which has recently been shown to be optimal assuming the Strong Exponential Time Hypothesis (SETH) [Bringmann, FOCS'14].To overcome the worst-case quadratic time barrier, restricted classes of curves have been studied that attempt to capture realistic input curves. The most popular such class are c-packed curves, for which the Fréchet distance has a (1 + ε)-appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Their algorithm runs in O(cn/ε + cn log n) time for curves in R d . Bringmann and Künnemann [3] improved the running time of the algorithm to O( cn √ ε log 2 (1/ε)+cn log n) for curves in R d . Assuming the Strong Exponential Time Hypothesis, Bringmann [2] showed that (i) for sufficiently small constants ε > 0 there is no (1 + ε)-approximation in time O((cn) 1−δ ) for any δ > 0, and (ii) in any dimension d ≥ 5 there is no (1 + ε)-approximation in time O((cn/ √ ε) 1−δ ) for any δ > 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their algorithm runs in O(cn/ε + cn log n) time for curves in R d . Bringmann and Künnemann [3] improved the running time of the algorithm to O( cn √ ε log 2 (1/ε)+cn log n) for curves in R d . Assuming the Strong Exponential Time Hypothesis, Bringmann [2] showed that (i) for sufficiently small constants ε > 0 there is no (1 + ε)-approximation in time O((cn) 1−δ ) for any δ > 0, and (ii) in any dimension d ≥ 5 there is no (1 + ε)-approximation in time O((cn/ √ ε) 1−δ ) for any δ > 0.…”
Section: Introductionmentioning
confidence: 99%
“…Existing algorithms [3,12] for computing the Fréchet distance between c-packed curves require that both curves are c-packed. An open problem is whether the Fréchet distance can be approximated efficiently when only one curve is c-packed.…”
Section: Introductionmentioning
confidence: 99%
“…These families of curves again include κ-bounded curves, but also c-packed curves. An improved algorithm for c-packed curves, which matches conditional lower bounds, was later given by Bringmann and Künnemann [5]. Gudmundsson et al [16] give a √ d-approximate algorithm for the case where the curves have sufficiently long edges (relative to their Fréchet distance) that runs in linear time.…”
Section: Introductionmentioning
confidence: 93%
“…A curve π is c-packed if for any ball B, the length of the portion of π contained in B is at most c times the radius of B. In their paper they considered the problem of computing the Fréchet distance between two c-packed curves and presented a (1 + ε)-approximation algorithm with running time O( cn ε + cn log n), which was later improved to O( cn √ ε log 2 (1/ε) + cn log n) by Bringmann and Künnemann [7]. Other models for realistic curves have also been studied.…”
Section: Introductionmentioning
confidence: 99%